การประดิษฐ์หุ่นแขนผู้ใหญ่แบบพกพา เพื่อฝึกการเจาะเลือด และการเปิดเส้นเลือดให้สารน้ำทางหลอดเลือดดำสำหรับนักศึกษาพยาบาล - บรรณสาร, เบญจพร (Journal of Thailand Nursing and Midwifery Council, 2017)
Objective: 1) To invent a portable low-cost adult arm model for practicing venipuncture skills and administration of peripheral intravenous cannulation; 2) To compare the efficiency of the portable adult arm model invented with the previous arm model for practicing venipuncture skills and administration of intravenous cannulation at the Faculty of Nursing, Thammasat University; 3) To compare venipuncture skills and administration of intravenous cannulation of nursing students before and after practicing with the portable adult arm model. Design: Research and development Procedure: The study was conducted in 4 stages: study about the invention of arm model ; model and scale development; using model; model development. The sample group used in this research was composed of 30 third-year nursing students in the Faculty of Nursing, Thammasat University who met the set inclusion criteria. The sample group will receive the portable adult arm model for practicing in their dormitories for a period of seven days. Data was collected by using an assessment scale on the efficiency of the portable adult arm model, an assessment scale on venipuncture skills and an assessment scale on administration of intravenous cannulation. The data obtained was analyzed by using descriptive statistics, paired t-test and Wilcoxon signed-ranks test. Results: The mean efficiency score for the portable adult arm model invented was higher than the mean efficiency score for the previous arm model with statistical significance (p < .001). Also, the mean score for venipuncture skills and administration of intravenous cannulation after practicing with the portable adult arm model invented was higher than before practicing with statistical significance (p < .001). Recommendation: The findings reveal the portable adult arm model are that was invented to be an efficient, feasible replacement for the previous arm model for venipuncture and the administration of intravenous cannulation in the Faculty of Nursing. Therefore, it should be used in teaching or extracurricular activities to provide students with skills in venipuncture and administration of peripheral intravenous cannulation.